EFFECT OF SOCIAL SUPPORT ON MINDFULNESS OF MEDICAL AND DENTAL STUDENTS - Ali, Muhammad; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2019)
Objective: To estimate the frequency of mindfulness and correlate the impact of social support on it in medical and dental students of Peshawar. Methodology: This cross-sectional study conducted from December 2017 to March 2018, included students of medical and dental colleges of Peshawar. Participants were selected by convenience sampling, and were asked to complete the Mindful Attention Awareness Scale (MAAS) and Social Support Rating Scale (SSRS). MAAS consists of 15 items and SSRS comprises of 10 questions with three subscales; subjective support, objective support and utilization of social support. The data was analyzed using SPSS version 20. Results: The mean age of the sample (n=624) was 20.9 ±1.6 years. Majority were male students 369 (59.1%) and most of the sample was collected from Private sector institutions (n=497, 79.6%), medical students (n=475, 76.1%) and from First year (n=236, 37.8%). The Cronbach's alpha reliability of MAAS in our study was 0.886. According to the responses of MAAS, there were 268 (42.9%) students having mindfulness. The responses on SSRC showed that 297 (47.6%) students do not have appropriate social support. The Pearson correlation showed that students who had better social support, showed more mindfulness (p=0.000). Conclusion: Every eighth medical student lacks appropriate social support and every sixth student having issues of mindfulness. However, a significant correlation was observed in both scales. MAAS can be reliably used in our setup.